The Influence of Post-Traumatic Growth on College Students’ Creativity During the COVID-19 Pandemic: The Mediating Role of General Self-Efficacy and the Moderating Role of Deliberate Rumination - Zeng, Wei; Zeng, Yuqing; Xu, Yanhua; Huang, Dongtao; Shao, Jinlian; Wu, Jiamin; Wu, Xingrou (Frontiers in Psychology, 2021)
Purpose: This study used a mediated mediation model to test the mediating effect of general self-efficacy on the relationship between post-traumatic growth (PTG) and creativity, as well as the moderating effect of deliberate rumination in the above mediating process, during the COVID-19 pandemic. Methods: A sample of 881 university students from Guangdong Province, China, were surveyed with the Posttraumatic Growth Inventory, the Runco Ideational Behavior Scale, the General Self-Efficacy Scale and the Deliberate Rumination Inventory. SPSS (23 version) and PROCESS (3.3 version) were used for correlation analyses, mediation analysis and moderated mediation analysis. Results: (1) PTG was positively correlated with creativity, self-efficacy and deliberate rumination. Creativity was positively correlated with self-efficacy and deliberate rumination. Deliberate rumination was positively correlated with self-efficacy. (2) Self-efficacy mediated the relationship between PTG and creativity. (3) Deliberate rumination moderated the second half of the path of “PGT → self-efficacy → creativity.” Conclusions: PTG affected creativity directly and also indirectly through self-efficacy. In particular, deliberate rumination moderated the relationship between self-efficacy and creativity, such that the association was stronger when the incidence of deliberate rumination was low. These results provide a more comprehensive understanding of the positive link between PTG and creativity.